Historical Redlining and Contemporary Racial Disparities in Neighborhood Life Expectancy. - Graetz, Nick; Esposito, Michael (Social Forces, 2023)
While evidence suggests a durable relationship between redlining and population health, we currently lack an empirical account of how this historical act of racialized violence produced contemporary inequities. In this paper, we use a mediation framework to evaluate how redlining grades influenced later life expectancy and the degree to which contemporary racial disparities in life expectancy between Black working-class neighborhoods and White professional-class neighborhoods can be explained by past Home Owners' Loan Corporation (HOLC) mapping. Life expectancy gaps between differently graded tracts are driven by economic isolation and disparate property valuation which developed within these areas in subsequent decades. Still, only a small percent of a total disparity between contemporary Black and White neighborhoods is explained by HOLC grades. We discuss the role of HOLC maps in analyses of structural racism and health, positioning them as only one feature of a larger public–private project conflating race with financial risk. Policy implications include not only targeting resources to formerly redlined neighborhoods but also the larger project of dismantling racist theories of value that are deeply embedded in the political economy of place.